(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study presents a comparative evaluation of the phytochemical composition and health-promoting potential of seven medicinal plant extracts Azadirachta indica, Curcuma longa, Allium sativum, Ocimum gratissimum, Vernonia amygdalina, Aloe barbadensis, and Moringa oleifera on the health biomarkers of broiler chickens. By integrating phytochemical profiling, biochemical assessment, hematological indices, and antimicrobial testing, this research provides a multi-dimensional understanding of phytogenic addictive. Phytochemical screening confirmed the presence of phenols, tannins, alkaloids, flavonoids, saponins, and cardiac glycosides in varying concentrations. Among the extracts, Ocimum gratissimum and Azadirachta indica contained the highest flavonoid and saponin levels, respectively. Vernonia amygdalina and Moringa oleifera exhibited superior effects on liver and kidney biomarkers, enhancing total protein while reducing urea and creatinine levels. Allium sativum notably improved hematological parameters such as hemoglobin concentration, while Azadirachta indica increased total white blood cell counts. Antimicrobial screening demonstrated that Moringa oleifera and Vernonia amygdalina possessed the strongest inhibition against pathogenic bacteria, including Salmonella spp., E. coli, and Klebsiella spp. These findings reveal the synergistic potential of medicinal plants as phytogenic feed additives to improve organ health, immunity, and microbial safety in poultry production. The comparative approach enhances understanding of plant specific effects and supports development of natural alternative to antibiotics in broiler chicken.